Transjugular intrahepatic portocaval shunting as a preparation phase for liver transplantation - P. G. Tarazov; D. A. Granov; A. A. Polikarpov; M. I. Generalov; I. O. Rutkin; O. A. Gerasimova; F. K. Zherebtsov (Трансплантология (Москва), 2018)
Objective: to assess the first results of transjugular intrahepatic portocaval shunting (TIPS) as a technique for preventing portal hypertension complications in patients in the period of waiting for a donor liver.Subjects and methods. TIPS was performed in 6 patients on the list of waiting for orthotopic liver transplantation (OLT). The indications for TIPS were current (n=1) or high-risk recurrent hemorrhages from the esophageal varices and stomach (n=4) and diuretic-resistant ascitis (n=1).Results. TIPS was successfully carried out in all the patients. The portovenous gradient was reduced by 2—3 times (to 9—12 mm Hg). A further follow-up revealed recurrent varicose hemorrhage or ascitis in none patients. Doppler study indicated that the shunt showed a good function. OLT was successfully made in 3 patients 2, 8, and 19 months after TIPS; one female patient had been waiting for OLT for 5 months; 2 patients died from sepsis and hepatic failure following 1 and 5 months, respectively.Conclusion. The first results suggest that in patients with hepatic cirrhosis complicated with portal hypertension, TIPS can be regarded as a safety bridge while waiting for a donor liver.